Feng–Liu-type fixed point result in orbital b-metric spaces and application to fractal integral equation - Nashine, Hemant Kumar; Dey, Lakshmi Kanta; Ibrahim, Rabha W.; Radenović, Stojan (Nonlinear Analysis: Modelling and Control, 2021)
In this manuscript, we establish two Wardowski–Feng–Liu-type fixed point theorems for orbitally lower semicontinuous functions defined in orbitally complete b-metric spaces. The obtained results generalize and improve several existing theorems in the literature. Moreover, the findings are justified by suitable nontrivial examples. Further, we also discuss ordered version of the obtained results. Finally, an application is presented by using the concept of fractal involving a certain kind of fractal integral equations. An illustrative example is presented to substantiate the applicability of the obtained result in reducing the energy of an antenna.